Mobpuod and gugumompi in the bereavement ritesand and traditions of the Kadazan in Penampang, Sabah - Rose Patsy Tibok; Andreas Totu; Romzi Ationg (Pennwell Corporation, 2020)
This study provides an overview of the concept of bereavement or mourning of the Kadazans in the district of Penampang, Sabah as reflected in the funeral rites and traditions observed by the community. Through in-depth interviews with informants within the Penampang Kadazan community, the study documents the series of observance and practices that are put in motion from the time of death to the completion of the bereavement period with specific focus on the rites expected of the living spouse of the deceased. The integral role of the gugumompi as ‘caretaker’ of the bereaved spouse and the person entrusted to ensure the adherence of these critical rites and traditions is highlighted. The study serves as a form of documentation and historical preservation for the many aspects of the mobpuod tradition and elements that define the Kadazan of Penampang, Sabah.